2021
DOI: 10.1111/1348-0421.12928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antibiotics on the viability of and toxin production by Clostridium botulinum

Abstract: Clostridium botulinum causes infant and adult intestinal botulism by colonizing in the intestine and producing botulinum neurotoxin (BoNT). Antimicrobial agents are not currently used for treatment due to the potential facilitation of BoNT production and bacterial cell lysis, which releases toxins into the intestinal lumen. In this study, we analyzed effects of four antibiotics on the viability of and BoNT production by four C. botulinum group I strains. Our results indicate that metronidazole rapidly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Studies have shown that food isolates of C. difficile possess MDR to tetracyclines, macrolides, penems and fluoroquinolones [71]. C. botulinum is not currently treated with antibiotic therapy due to the potential for BoNT release post bacterial cell lysis [15]. The treatment for BoNT is an equine anti-BoNT antiserum; however, it is not suitable for infant patients and has a risk of anaphylaxis [15].…”
Section: Antibiotic Treament Of Clostridioides Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that food isolates of C. difficile possess MDR to tetracyclines, macrolides, penems and fluoroquinolones [71]. C. botulinum is not currently treated with antibiotic therapy due to the potential for BoNT release post bacterial cell lysis [15]. The treatment for BoNT is an equine anti-BoNT antiserum; however, it is not suitable for infant patients and has a risk of anaphylaxis [15].…”
Section: Antibiotic Treament Of Clostridioides Speciesmentioning
confidence: 99%
“…C. botulinum is not currently treated with antibiotic therapy due to the potential for BoNT release post bacterial cell lysis [15]. The treatment for BoNT is an equine anti-BoNT antiserum; however, it is not suitable for infant patients and has a risk of anaphylaxis [15]. Infant patients receive Botulism Immune Globulin Intravenous, BabyBIG, in the United States.…”
Section: Antibiotic Treament Of Clostridioides Speciesmentioning
confidence: 99%
See 1 more Smart Citation